2019
DOI: 10.1073/pnas.1900152116
|View full text |Cite
|
Sign up to set email alerts
|

Apelin protects against abdominal aortic aneurysm and the therapeutic role of neutral endopeptidase resistant apelin analogs

Abstract: Abdominal aortic aneurysm (AAA) remains the second most frequent vascular disease with high mortality but has no approved medical therapy. We investigated the direct role of apelin (APLN) in AAA and identified a unique approach to enhance APLN action as a therapeutic intervention for this disease. Loss of APLN potentiated angiotensin II (Ang II)-induced AAA formation, aortic rupture, and reduced survival. Formation of AAA was driven by increased smooth muscle cell (SMC) apoptosis and oxidative stress inApln−/y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Building on these findings, further studies could substitute the amino acids at the neprilysin cleavage sites in [Pyr 1 ]apelin-13 with unnatural amino acids to improve its resistance to degradation. Indeed, it was recently shown that infusion of neprilysin resistant apelin-17 in an established mice model of abdominal aortic aneurysm ameliorated the adverse aortic remodelling and aneurysm formation 27 . Such a strategy was also demonstrated to significantly increase the resistance of [Pyr 1 ]apelin-13 and apelin-17 to ACE2 activity 22,23 , suggesting that this could potentially be a mechanism to improve plasma stability of apelin-based therapeutics for clinical indications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on these findings, further studies could substitute the amino acids at the neprilysin cleavage sites in [Pyr 1 ]apelin-13 with unnatural amino acids to improve its resistance to degradation. Indeed, it was recently shown that infusion of neprilysin resistant apelin-17 in an established mice model of abdominal aortic aneurysm ameliorated the adverse aortic remodelling and aneurysm formation 27 . Such a strategy was also demonstrated to significantly increase the resistance of [Pyr 1 ]apelin-13 and apelin-17 to ACE2 activity 22,23 , suggesting that this could potentially be a mechanism to improve plasma stability of apelin-based therapeutics for clinical indications.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that apelin peptides are very labile in plasma with a half-life of less than 1-5 minutes in vitro [20][21][22][23][24] . This plasma instability has to date been attributed the enzymatic activity of neprilysin 25 and angiotensin converting enzyme II (ACE2) [22][23][24] , and more recently plasma kallikrein 26,27 . Similarly, another recent study reported more rapid degradation of [Pyr 1 ]apelin-13 in rat and mouse plasma when compared to dog, monkey and human plasma in vitro 28 .…”
mentioning
confidence: 99%
“…Ang II-mediates up-regulation of Apelin (APLN), which in turn up-regulates ACE2, leading to conversion of Ang II by ACE2 into the protective Ang 1-7 peptide [14,15]. The APLN pathway has emerged as a major peptide hormone pathway with APLN widely expressed in mammals [16] and ACE2 is an important target of APLN action in the vasculature [17]. The regulatory loop also functions such that apelin 13 is required for ACE2 expression [18][19][20].…”
Section: Ras In Gitelman's and Bartter's Syndromesmentioning
confidence: 99%
“…In addition to Ang II, apelin is another catalytic substrate for ACE2 and is considered an inotropic and cardioprotective peptide [ 82 , 83 ]. Among apelin peptides, apelin-13 is the most abundant in human plasma and cardiac tissue, and it exists predominantly under its pyroglutamylated form (Pyr-apelin-13) [ 84 ].…”
Section: Activating the Peptidase Function Of Ace2 For Lung Protecmentioning
confidence: 99%
“…In ACE2 knockout mice, hypotensive action of Pyr-apelin-13 was enhanced, with higher apelin levels in plasma. In turn, apelin-13, via activation of G protein–coupled receptor, the apelin receptor (APJ), increased ACE2 promoter activity in vitro, and upregulated ACE2 expression in failing hearts in vivo [ 83 ]. Moreover, apelin-13 treatment also increased cardiac contractility and ACE2 levels in AT1R-deficient mice, which demonstrate an antagonistic relationship between the RAS and apelin [ 83 ].…”
Section: Activating the Peptidase Function Of Ace2 For Lung Protecmentioning
confidence: 99%